Students' Decisions to Use an eLearning System: A Structural Equation Modelling Analysis - Abbad, Muneer; Morris, David; Al-Ayyoub, Abdel-Elah; Abbad, Jumma'a (International Journal of Emerging Technologies in Learning (iJET), 2009)
This research investigates and identifies some of the major factors affecting studentsâ?? adoption of an e-learning system at Arab Open University in Jordan. E-learning adoption is approached from the information systems acceptance point of view. An extended version of the Technology Acceptance Model (TAM) was developed to investigate the underlying factors that influence studentsâ?? decisions to use an e-learning system. The proposed model uses the actual use of an e-learning system. It is different from most of the prior TAM studies, which only used a single dependent variable (intention to use). The model was estimated using Structural Equation Modelling (SEM). The final models derived from this study indicated that beliefs of usefulness and ease of use partially mediate the relationship between external factors and intention to use and actual use of e-learning systems.